Copper-catalysed asymmetric allylic alkylation of alkylzirconocenes to racemic 3,6-dihydro-2H-pyrans - Rideau, Emeline; Fletcher, Stephen P. (Beilstein Journal of Organic Chemistry, 2015)
Asymmetric allylic alkylation is a powerful reaction that allows the enantioselective formation of C–C bonds. Here we describe the asymmetric alkylation of alkylzirconium species to racemic 3,6-dihydro-2H-pyrans. Two systems were examined: 3-chloro-3,6-dihydro-2H-pyran using linear optimization (45–93% ee, up to 33% yield, 5 examples) and 3,6-dihydro-2H-pyran-3-yl diethyl phosphate with the assistance of a design of experiments statistical approach (83% ee, 12% yield). 1H NMR spectroscopy was used to gain insight into the reaction mechanisms.
Keywords: allylic alkylation; asymmetric catalysis; copper; design of experiments; dynamic kinetic asymmetric transformation; heterocycles; Schwartz reagent